KOMPETENSI PERADILAN AGAMA DALAM INTERPRETASI HUKUM KELUARGA ISLAM DI INDONESIA - Shobirin, Shobirin (UIN Sunan Kudus, 2015)
Restrictions study area in this article, the starting point of three scholarly foundation, the foundation of ontology related to the object of study, epistemological ground with regard to the method used in the study and axiology berkaiatan foundation with the purpose or significance of the study. The object of study in this article is the competence of the Religious Court in the interpretation of Islamic family law in Indonesia, covering permasalahn Interpretation of Family Law Islamic Religious Courts Indonesia, procedures Interpretation of Family Law Islamic Religious Courts Indonesia, Judgment of Religious Courts in Indonesia there Interpretation Law and competent in the interpretation of Islamic Family Law in Indonesian Religious Courts. The method used, the study included a kind of normative legal studies approach to the blade, then the method of analysis, there are three, namely; (1) political approach; (2) statue approach; (3) analytical approach. The data source materials normative, ie competence Religious Court of Indonesia and all sources of Islamic family law that is set in the regulations and legislation arranged in hierarchical. Data collection techniques to study the document. This study, including qualitative assessment of normative, the analytical descriptive analysis (explanatory). Theoretical framework used,, ie at the level of grand theory using the theory of ijtihad, the middle level of theory using the theory of law and society and on the plains applied theory using the theory of Islamic Sharia judicial system. While the significance of this study is to find the source of the law, the legal function and purpose of law. The results in this study, which was to find the nature of legal interpretation, legal interpretation procedures, problems that are interpreted in the Religious and who are competent to interpret the Islamic family law in Indonesian Religious Courts.